An evaluation of the effectiveness of laptop computers in science classrooms - Stolarchuk, Eddie O. (Curtin University, 1997)
Numerous educational research studies have shown that students perceptions of teacher-interpersonal behaviour and classroom environment are positively associated with students attitude to science and students cognitive achievement in science. Laptop computers have become increasing popular in science classrooms since the late 1980s; however, their effects on students perceptions of teacher interpersonal relationships or classroom environment have not been studied.The aim of this study was to assess the effectiveness of laptop computers in science classrooms, in terms of the effects laptops had on students perceptions of teacher-student interpersonal behaviour and classroom environment. Students attitude to science and their cognitive achievement in science were also assessed.Student data were collected from 433 grades 8 and 9 science laptop students in 23 classrooms, in 14 Independent schools, in four Australian states. Both quantitative and qualitative data were collected.The study confirmed the reliability and validity of the QTI and ICEQ for use in science laptop classrooms, described students perceptions of teacher-student interpersonal behaviour and classroom environment in science laptop classrooms and identified associations between students perceptions of teacher-student interpersonal behaviour and classroom environment with each of the student outcomes. The attitudinal outcomes were found to be more strongly associated with both perceptual areas, than were the cognitive achievement outcomes.The study also found that there was a difference in the way science laptop and non-laptop students perceived teacher-student interpersonal behaviour and classroom environment, but that there was no significant difference I the attitudinal and cognitive achievement outcomes between science laptop and non-laptop students.